Avaliação da cognição social em pacientes com transtorno bipolar - Flávia da Mata Chiácchio Leite (2017)
Introduction: Patients with type I bipolar disorder present cognitive impairment. One domain the remains poorly explored is social cognition. The main impaired processes of social cognition in type I bipolar disorder are emotion recognition and theory of mind. Impairments in theory of mind and emotion recognition seem to be associated with worse functionality in bipolar patients. Objective: To evaluate social cognition and other cognitive domains of patients with type I bipolar disorder in euthymia compared to healthy controls and correlate with functionality, clinical variables and sociodemographic characteristics. Method: In a cross-sectional design, patients and controls were evaluated using the Mini Mental State Examination (MMSE), the Frontal Assessment Battery (FAB), the Positive and Negative Syndrome Scale for Schizophrenia (PANSS), the Brief Assessment of Cognition in Affective Disorders (BAC-A), the short version of the scale for social cognition evaluation Social Emotional Assessment (Mini SEA) and the Functioning Assessment Short Test (FAST). Results: Patients performed significantly worse in MMSE (p= 0,003), FAB (p= 0,001), BAC-A (z-score: -1,05) and Mini-SEA's theory of mind (p= 0,003) and emotion recognition (p< 0,001) tasks, in addition to worse functionality (p< 0,001). There was no correlation between social cognition and functionality. Conclusion: Type I bipolar disorder presents impaired social cognition in addition to functional impairment. Social cognition does not seem to be related to functionality on type I bipolar disorder patients in euthymia.